Carryover Effects in Sibling Comparison Designs. Issue 6 (November 2016) - Sjölander, Arvid; Frisell, Thomas; Kuja-Halkola, Ralf; Öberg, Sara; Zetterqvist, Johan
Abstract : A convenient way of dealing with confounding is the sibling comparison design, where the outcome in exposed individuals is compared with the outcome in their unexposed siblings. The standard analysis of sibling comparison designs assumes that the exposure and outcome of an individual do not affect the exposure and outcome of his/her siblings, sometimes referred to as an absence of sibling carryover or contagion effects. Unfortunately, there are many situations where carryover effects are likely to be present. In this article, we explore the consequences of carryover effects for sibling comparison designs. We show, using causal diagrams, when and why carryover effects lead to bias, and we investigate the sign and magnitude of this bias under various scenarios. Abstract : Supplemental Digital Content is available in the text.